2012
DOI: 10.1155/2012/193639
|View full text |Cite
|
Sign up to set email alerts
|

CFD Study of Industrial FCC Risers: The Effect of Outlet Configurations on Hydrodynamics and Reactions

Abstract: Fluid catalytic cracking (FCC) riser reactors have complex hydrodynamics, which depend not only on operating conditions, feedstock quality, and catalyst particles characteristics, but also on the geometric configurations of the reactor. This paper presents a numerical study of the influence of different riser outlet designs on the dynamic of the flow and reactor efficiency. A three-dimensional, three-phase flow model and a four-lump kinetic scheme were used to predict the performance of the reactor. The phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 41 publications
(69 reference statements)
2
16
0
6
Order By: Relevance
“…The reaction rates from gasoline to gas and coke of particles in the cluster were higher than that of the isolated particles. Gabriela C. Lopes et al (2012) [31],presented a three dimensional ,three phase flow model and a four lump kinetic base model to study the influence of different riser outlet bend designs on the dynamics of the flow and reactor efficiency .Results show that small changes in the outlet configuration had a significant on the flow patterns and on reactions yields. The use of abrupt exits results in solids ,back mixing which enhanced the residence time of the catalyst and increased its concentration near the top of the riser.…”
Section: Modeling Of Riser Reactor 31 Riser Kineticsmentioning
confidence: 99%
“…The reaction rates from gasoline to gas and coke of particles in the cluster were higher than that of the isolated particles. Gabriela C. Lopes et al (2012) [31],presented a three dimensional ,three phase flow model and a four lump kinetic base model to study the influence of different riser outlet bend designs on the dynamics of the flow and reactor efficiency .Results show that small changes in the outlet configuration had a significant on the flow patterns and on reactions yields. The use of abrupt exits results in solids ,back mixing which enhanced the residence time of the catalyst and increased its concentration near the top of the riser.…”
Section: Modeling Of Riser Reactor 31 Riser Kineticsmentioning
confidence: 99%
“…Lopes et al (2011) showed in their work the importance of using three-dimensional models to predict the phenomena that occur in the riser. Then Lopes et al (2012) and Barbosa et al (2012) used threedimensional models to study the influence of different riser outlet and inlet geometries, respectively. It was observed that small changes in the riser geometry influence the hydrodynamics and the product profile.…”
Section: Introductionmentioning
confidence: 99%
“…La simulación numérica de este proceso, tratando de predecir el comportamiento del flujo gas-sólidos, evaluando los perfiles de concentración y velocidad de los sólidos así como el perfil de temperatura, se han venido realizando desde las últimas dos décadas del siglo pasado, fundamentalmente variando la geometría y se ha observado que al variarla se modifican los perfiles de flujo a lo largo de todo el riser (Huilin et al, 2006;Hamzehei y Rahimzadeh, 2010;Chalermsinsuwan et al, 2010;Vegendla, et al, 2011, Lopes et al, 2012; pero a la fecha no se ha realizado un estudio donde se propongan dos salidas colocadas asimétricamente como el estudio mostrado en este trabajo.…”
Section: Introductionunclassified